The Effect of Using Genially on Eighth-Grade Students’ Understanding of Mathematical Concepts in the Pythagorean Theorem - Zulfa Dwi Yanti Tangio; Sumarno Ismail; Auli Irfah (Faculty of Teacher Training and Education, 2026)
This study aims to determine the effect of using Genially media on students' understanding of mathematical concepts in Pythagorean theorem material for eighth grade. This research is a quantitative study with a quasi-experimental method using a pretest-posttest control group design. The population was all eighth-grade students of SMP Negeri 2 Limboto. The sample was selected using random sampling technique, consisting of an experimental class of 25 students who learned using Genially media and a control class of 25 students who learned using PowerPoint media. The instrument used was an essay test consisting of 10 questions that had been validated and declared reliable with Cronbach’s Alpha coefficient of 0.8751. The results showed that the average posttest score of the experimental class was 26.24, higher than the control class which was 21.56. Hypothesis testing using independent samples t-test obtained , while at significance level so was rejected and was accepted. The effect size calculation using Cohen's d yielded a value of 1.06 which falls into the strong effect category. The conclusion of this study is that there is a strong effect of using Genially media on students' understanding of mathematical concepts in Pythagorean theorem material.